Bottom‐Up Instructive Quality Control in the Biofabrication of Smart Protein Materials. (28th October 2015) - Rueda, Fabián; Céspedes, María Virtudes; Conchillo‐Solé, Oscar; Sánchez‐Chardi, Alejandro; Seras‐Franzoso, Joaquin; Cubarsi, Rafael; Gallardo, Alberto; Pesarrodona, Mireia; Ferrer‐Miralles, Neus; Daura, Xavier; Vázquez, Esther; García‐Fruitós, Elena; et al.
Abstract : The impact of cell factory quality control on material properties is a neglected but critical issue in the fabrication of protein biomaterials, which are unique in merging structure and function. The molecular chaperoning of protein conformational status is revealed here as a potent molecular instructor of the macroscopic properties of self‐assembling, cell‐targeted protein nanoparticles, including biodistribution upon in vivo administration.